Avaliação do sistema viário urbano a partir da opinião dos usuários - Medeiros, Rafaela de Sousa (2022)
The urban space is composed of several infrastructure systems, which interact with each other allowing the city to function. In the road system, different transportation modes share the road, with different needs related to this space. Therefore, it is necessary to understand the perception of the users, so the roads offer a good service to all modes. This work sought to evaluate the quality of the urban road system, according to the perception of car drivers, pedestrians and cyclists. The perception of these users was collected from questionnaires applied in the city of Joao Pessoa-PB, in order to classify the relevance of aspects of the urban environment for the quality of trips made in the city. The responses were applied to the Method of Successive Intervals, to define the weights of the criteria and sub-criteria used in the evaluation of the roads. The conditions of the road pavement and of the sidewalk were the most important elements for car drivers and pedestrians, respectively. For cyclists, traffic control elements represented the most relevant factor for the quality of the trip. Furthermore, the criteria and sub-criteria were applied in the evaluation of three roads of Joao Pessoa-PB, to test their applicability. It was seen that the use of these elements, associated with the parameters to assign the grades, made it easy and quick to evaluate the condition of the roads, offering an overview of the existing quality of service.